Impact of COVID-19 on the mental health of adolescents and youth in Nairobi, Kenya - Gichangi, Peter B.; Byrne, Meagan E.; Thiongo, Mary N.; Waithaka, Michael; Devoto, Bianca; Gummerson, Elizabeth; Wood, Shannon N.; Anglewicz, Philip; Decker, Michele R. (Frontiers in Psychiatry, 2024)
Objective: To report on the mental health status of adolescents and youth in relation to the pandemic in Nairobi County, Kenya.Methodology: This was a mixed-methods study with cross-sectional quantitative and qualitative components conducted in Nairobi County, Kenya from August to September 2020. The quantitative survey involved phone interviews of n=1,217 adolescents and youth. Qualitative components included virtual focus group discussions (FGDs) with adolescents and youth (n=64 unmarried youths aged 16-25 years, across 8 FGDs) and youth-serving stakeholders (n=34, across 4 FGDs), key informant interviews (n=12 higher-level stakeholders from Ministries of Health, Gender, and Education), and indepth interviews with youth (n=20) so as to examine the COVID-19 impact on mental health.Results: Among the participants, 26.6% of young men and 30.0% of young women reported probable depressive symptoms, of whom 37.7% of young men and 38.9% of young women reported little interest or pleasure in doing various activities. Hopelessness and feeling down nearly every day was additionally reported by 10.7% of young women and 6.3% of young men. Further, about 8.8% of young men and 7.6% of young women reported they could not get the emotional help and support they may need from people in their life. Multivariable regression results showed an association between depressive symptoms and reduced working hours due to COVID-19 and increased intimate partner violence. Additionally, the results show that respondents with higher emotional help and support were less likely to report depressive symptoms. Qualitative results confirm the quantitative findings and exemplify the negative behavior arising from the impact of adherence to COVID-19 prevention measures.Conclusions: Mental health issues were common among adolescents and youth and may have been augmented by isolation and economic hardships brought about by COVID-19 restrictions. There is a need for concerted efforts to support adolescents and young people to meet their mental health needs, while considering the unique variations by gender. There is need to urgently strengthen the mental health system in Kenya, including via integrating psychosocial support services in communities, schools, and healthcare services, to ensure adolescents and young persons are not left behind.